GLOBAL ENGLISH ACCENTS AND NON-NATIVE ENGLISH TEACHERS - Oleg B. Tarnopolsky; Svitlana D. Storozhuk (Alfred Nobel University Publisher, 2021)
The article is a theoretical study of the issue of non-native English speakers and, in particular, nonnative English teachers' accent peculiarities and whether these can be an obstacle for employing the latter as teachers of EFL (English as a Foreign Language taught in non-English-speaking countries) or ESL (English as a Second Language taught in English-speaking countries). In the paper, an attempt is made to prove that, under certain conditions, such accent peculiarities can be considered not as qualified non-native English teachers' shortcomings but as an asset of a kind. In that respect, the notion of global English accents is introduced, which are considered as normative accents for English as an international, or rather global/ planetary, language of international/intercultural communication taught to all the learners of EFL and ESL. It is claimed that special measures should be taken for the native and non-native speakers of English to become accustomed and adapted to hearing such diverse accents quite frequently even in their home countries. Both the native and non-native English speakers the world over need to be taught and get accustomed to perceive the global English accents as something totally normal and acceptable as long as they do not make communication in English incomprehensible or comprehensible with difficulty. The advantages of non-English teachers with their accent peculiarities are discussed when teaching English not only to EFL but ESL students as well, and it is shown that they can be a great help in inuring both nonnative and native speakers of English to hearing the variety of global English accents. It is indicated that relevant training and mutual cooperation of both non-native and native teachers of English is required for achieving this goal.